﻿Application of 99mTc-UBI 29–41 scintigraphy in knee periprosthetic infection diagnosis - Kiamanesh, Zahra; Ayati, Narjess; Alavi, Royasadat; Gharedaghi, Mohammad; Aryana, Kamran (Nuklearmedizin - NuclearMedicine, 2019)
Aim In recent years, the use of total knee arthroplasty (TKA) is considered a safe and cost-effective orthopedic procedure for alleviating the chronic pain and treatment of progressive osteoarthritis. This procedure may have some complications including periprosthetic infection as the most serious and aseptic loosening as the most common one. Differentiating between these entities is important because each has a different therapeutic approach. This study was conducted to investigate the ability of 99mTC-UBI scan to distinguish septic from aseptic loosening in a painful knee prosthesis.Methods 34 patients with painful knee prostheses were included. The 99mTC-UBI scan was done immediately after IV administration of 99mTC-UBI in early dynamic and 30-minute static images. Time-activity curve (TAC) was drawn for all patients and target to non-target ratio (T/NT) was calculated on 30-minute images. The final diagnosis was confirmed by surgical findings, microbiologic culture results or active clinical follow up.Results Using TAC analysis, 24 99mTC-UBI scans were considered negative and 10 positive for an infectious process. Sensitivity, specificity, negative and positive predictive values were 56 %, 80 %, 83 %, and 50 %, respectively. T/NT ratio analysis on 30-minute static images demonstrated 9 positive and 25 negative patterns, with a cut off value of 1.83 for the T/NT ratio. The sensitivity, specificity, negative and positive predictive values, and accuracy of this test modality were all 100 %.Conclusions Our findings show 99mTc-UBI scan is an excellent clinical diagnostic test for differentiating septic from aseptic loosening of the knee prostheses with perfect sensitivity and specificity. Highly accurate results were obtained only 30 minutes after injection.
Keywords: Total knee arthroplasty; 99mTC-UBI scintigraphy; periprosthetic infection; prosthetic loosening